Improving the hot corrosion resistance of boiler tube steels by detonation gun sprayed coatings in actual boiler of thermal power plant. Issue 4 (1st July 2019) - Singh, Vikramjit; Goyal, Khushdeep; Goyal, Rakesh
Abstract : Purpose: This paper aims to investigate the hot corrosion behavior of Ni-Cr and Cr3C2-NiCr coatings, deposited on T11, P91 boiler steels by detonation gun spray coating (D-Gun) process to enhance high temperature corrosion resistance. Design/methodology/approach: Hot corrosion studies were conducted in secondary super heater zone of boiler at 900 °C for 10 cycles on bare and D-Gun coated steel specimens. The microhardness and porosity values of as-sprayed coatings were measured before exposing the specimens in the boiler environment. Each cycle consisted 100 h of heating in the boiler environment followed by 20 min of cooling in air. The weight change measurements were performed after each cycle to establish the kinetics of corrosion using thermogravimetric technique. X-ray diffraction, SEM techniques were used to analyze the corroded specimens. Findings: Uncoated boiler steel experienced higher weight loss. The Cr3C2-NiCr coating was found to be more protective than Ni-Cr coating. The phases revealed the formation of oxide scale on coated specimens, mainly consist of nickel and chromium, which are reported to be protective against the hot corrosion. Originality/value: There is very limited reported literature on hot corrosion behavior of Ni-Cr and Cr3C2-NiCr coatings deposited on the T11 and P91 substrates by detonation gun (D-gun) spray technique. T11 and P91 alloy steels have been chosen for this study because these two alloys are used to manufacture boiler tubes used in Indian thermal power plants.